2002
DOI: 10.2169/internalmedicine.41.1158
|View full text |Cite
|
Sign up to set email alerts
|

Acute Interstitial Nephritis with Polyclonal B Cell Infiltration and Development of Mantle Cell Lymphoma.

Abstract: A 69-year-old man with proteinuria, hematuria and abnormal renal and hepatic function developed acute renal failure. His clinical and laboratory examinations showed splenomegaly, edema, anemia and polyclonal hypergammaglobulinemia with high IgG levels. Renal biopsy showed interstitial nephritis with predominant B cell and plasma cell infiltration without monoclonality. After corticosteroid treatment, the patient showed remission in clinical symptoms and laboratory findings. However, one year later, he develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The effect of corticosteroids on interstitial nephritis associated with CD was transient [23] or ineffective [21,22] in three cases, and only one case with the hyaline vascular type was successfully treated with corticosteroids [24]. Another case of possible MCD with acute interstitial nephritis with polyclonal B-cell infiltration successfully treated by corticosteroid therapy has been reported that patient developed mantle cell lymphoma 1 year later, but the histological diagnosis of MCD was not made [25]. In our case, the treatment of interstitial nephritis was effective, and it did not recur throughout the clinical course since the kidney at autopsy showed no evidence of interstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of corticosteroids on interstitial nephritis associated with CD was transient [23] or ineffective [21,22] in three cases, and only one case with the hyaline vascular type was successfully treated with corticosteroids [24]. Another case of possible MCD with acute interstitial nephritis with polyclonal B-cell infiltration successfully treated by corticosteroid therapy has been reported that patient developed mantle cell lymphoma 1 year later, but the histological diagnosis of MCD was not made [25]. In our case, the treatment of interstitial nephritis was effective, and it did not recur throughout the clinical course since the kidney at autopsy showed no evidence of interstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…As in this case, virtually all of Mantle cell lymphomas are associated with a t(11;14) translocation resulting in overexpression of the cyclin D1 gene. [1] Case reports of patients with MCL and glomerulonephritis [2][3][4][5] have previously been described. All of the cases reported by previous groups [2][3][4][5] presented with acute renal failure, as did the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Case reports of patients with MCL and glomerulonephritis [2][3][4][5] have previously been described. All of the cases reported by previous groups [2][3][4][5] presented with acute renal failure, as did the present patient. In all patients previously reported, renal disease and function correlated well with the lymphoma activity, and when treated with chemotherapy, the renal disease and function improved.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour‐related conditions such as hypercalcaemia, paraneoplastic glomerulonephritis and tumour lysis syndrome after chemotherapy may cause ARF. Renal infiltration in malign lymphomas may involve the interstitium, but rarely causes ARF 3,4 . We described a patient presented with ARF, whose renal biopsy showed interstitial nephritis with atypical lymphoid infiltration with typical markers of cyclin‐D1 for mantle cell lymphoma (MCL).…”
mentioning
confidence: 99%